International Perception of Competence, Education, and Training Needs Among Biomedical Professionals Involved in Medicines Development - Kyoko Imamura; Domenico Criscuolo; Anna Jurczynska; Gustavo Kesselring; Peter Stonier; Tatsushi Tsuda; Honorio Silva (Frontiers Media S.A., 2019)
The development of new medicines today, requires a multi-professional workforce, both in industry and the clinical research arena. Pharmaceutical physicians (PPs) and medicines development scientists (MDS) need a certain level of competence, achieved through on-the-job experience, with a postgraduate education foundation and continuous professional development programs. In order to assess the self-perception of competence, education and training needs, an on-line questionnaire based on the seven domains of competence, developed by IFAPP-PharmaTrain, was prepared and distributed among PPs and MDS members of IFAPP's affiliated professional associations in countries with facilities for postgraduate education. The data collection was run over a fixed period of three months in Japan, Italy, Brazil, and Spain during 2017. Results indicate low but variable levels of perceived competence for the various domains as well as seniority in the job. All respondents declared a significant need for continuing professional development in all domains. These results corroborate and support the continuous efforts, put in place by IFAPP and the PharmaTrain Federation, to foster the development of accredited education and training among professionals involved in medicines development.